The Academic Performance of First Year University Students: A Comparative Analysis - Perkins, Stanley A. (Canadian Journal of Counselling and Psychotherapy, 2012)
The purpose of this paper was to compare the academic performance of regularly admitted first-year university students who were arranged in three groups according to their average performance on senior matriculation examinations with that of "mature" students who did not meet regular academic admission requirements. The results showed that while the "mature" students had scored some of the lowest results on the College Qualification Test, they were the second highest of the four groups for the Fall, Spring, and Accumulative Grade Point average. The data suggests that if "mature" students concentrate on their studies in the arts and humanities they may be quite successful.